Proposed guidelines for the construction of theses abstracts of the University of the Philippines' Institute of Library and Information Science - Tenmatay, Tyran Rex (School of Library and Information Studies, University of the Philippines Diliman, 2006)
An abstract is a brief summary of the research. A summary however brief, contains the most important aspects of study done by students and professional researchers alike. To better serve the researchers, a uniform abstracting guideline needed to be created to replace the too simple, "not to exceed 2 pages" used by the Institute of Library and Information Science Thesis/Special Problem Manual dated July 2003.This study did a user needs assessment of the students of the Institute of Library and Information Science in relation to their theses abstracting needs and expectations by using a checklist questionnaire. The data gathered was then presented to a professional abstractor and refined into a more concrete guideline specifying the content and length of the abstract.